An analysis of the human resources development policy framework 2012 – the case of the Department of Public Service Management, office of the prime minister (OPM) in Namibia - Shikokola, Matilde-Sirkka Patemoshela (Stellenbosch : Stellenbosch University, 2024)
Thesis (MPA)--Stellenbosch University, 2024.